Pedagogias da beleza: a história da educação do corpo feminino no Correio da Manhã (1925-1972) - Neiva, Renata Maria de Oliveira (2018)
A thin and young body; a beauty standard repeatedly propagated for almost half of a century by one of the most influential newspapers in Brazil for a significant part of the 20th century – Correio da Manhã (1901-1974), published in Rio de Janeiro, but that circulated across Brazil. As the pages of this so called feminine publication are turned, since 1925, when we find the first sections that remained periodical, until 1972, when the last publications were released, we grasp how the recurrent reading of these supplements contributed to the education of women in Brazilian cities, which belonged to high and middle classes and searched a certain lifestyle in this world. In the wake of thoughts of Le Breton, Lipovetsky, Perrot and Vigarello, we shine a light over an education ruled, therefore, by an ideal of presence shaped by “should-be”. Thus, we deal with pedagogies of beauty because we understand that there are many pedagogy forms in circulation beyond school walls. Belonging to the History and Historiography field, this research was inspired by History of Women's Education, Cultural History of the Press, as well as Bakhtin's discourse analysis. Among the genres published in the newspaper, we prioritized reportings, columns and advertising. The study, therefore, enabled us to think the newspaper as a totality of discourses, the set of a text that assumes unity of meaning. A totality formed by verbal and visual segments that insist on the same formula – a promise of acceptance and happiness that crossed decades and still reverberates in the 21st century, whether through print vehicles or in virtual networks relationships.